Climate Obstruction in Germany: Hidden in Plain Sight? - Achim Brunnengräber; Moritz Neujeffski; Dieter Plehwe (Climate Obstruction across Europe, 2024)
Since the inclusion of ecological considerations in Germany's social market economy model in the 1990s and the approval of the Renewable Energy Sources Act (RESA) in 2000, the debate on climate policy in Germany has intensified. Opposition to ambitious targets currently focuses on delaying the Energiewende, the ongoing, country- and sector-wide transition to renewable energy. This opposition comprises both climate change deniers and actors who want to preserve Germany's centralized fossil fuel energy structures. Recent policy adjustments have included the expansion for the building of the infrastructure for liquefied natural gas and weakening of laws mandating decarbonization in heating. Even greater efforts have been made to delay effective carbon reduction strategies, such as advocating carbon offsets and weakening auto emissions standards. This chapter identifies and analyzes German companies', politicians', and interest groups' climate obstruction activities, which centre on using think tanks and nongovernmental organizations to influence public opinion.
Keywords: 300